And mockery: a two-layer account. (July 2015) - Iwata, Seizi
Abstract: When the utterance "I'm the President, " which is seriously meant, is responded to with "And I'm the First Lady, " the validity of that utterance is challenged with sarcasm. This type of and locution, referred to as and mockery, has been analyzed in terms of quotation of the illocutionary act (Haiman, 1998) or metarepresentation/echo (Noh, 2000), but both analyses are problematic. Rather, a two-layer account, which is built upon Clark's (1996) theory of non-serious linguistic acts, better accounts for why and mockery conveys what it does. The proposed account naturally extends to variations involving an echo question, an echo declarative, or an if conditional. Furthermore, the proposed account sheds new light on the debate between echoic theory and pretense theory, which have been two major theories of verbal irony. Highlights: A two-layer account of sarcastic irony, building onClark (1996), is proposed. The account extends to several variants (echo question, echo declarative, or if conditional). A new light is shed on the debate between echoic theory and pretense theory.